1989
DOI: 10.1093/geronj/44.3.m77
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Agitation in a Nursing Home

Abstract: Agitation is a significant problem for elderly persons, their families, and their caregivers. This study describes the agitated behaviors of 408 nursing home residents. Nurses who were familiar with the residents used a 7-point scale to rate how often each resident manifested 29 agitated behaviors. Each resident was rated independently by three nurses, one from each of the three nursing shifts. Results showed that agitated behaviors occurred most often during the day shift (i.e., when residents were most activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
863
4
14

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,143 publications
(907 citation statements)
references
References 0 publications
26
863
4
14
Order By: Relevance
“…The Cohen-Mansfield Agitation Inventory short form (14 items) (Cohen-Mansfield et al, 1989a) was completed by the subject's keyworker to assess the frequency of agitated behaviour at the care unit. (Cohen-Mansfield et al, 1989b;Cohen-Mansfield, 1986) -The subject's behaviour was observed and rated using the ABMI with reference to 3-minute samples before, immediately after, 15 minutes after and 30 minutes after each therapy session.…”
Section: Methodsmentioning
confidence: 99%
“…The Cohen-Mansfield Agitation Inventory short form (14 items) (Cohen-Mansfield et al, 1989a) was completed by the subject's keyworker to assess the frequency of agitated behaviour at the care unit. (Cohen-Mansfield et al, 1989b;Cohen-Mansfield, 1986) -The subject's behaviour was observed and rated using the ABMI with reference to 3-minute samples before, immediately after, 15 minutes after and 30 minutes after each therapy session.…”
Section: Methodsmentioning
confidence: 99%
“…The availability of general BPSD scales such as the Neuropsychiatric Inventory (NPI), as well as specific scales such as Cohen-Mansfield Agitation Inventory, 15 has not allowed yet unequivocal demonstration of benefit in severe stages of AD. New methods of analysis of behavior have been proposed, 16,17 and will likely be more successful in defining categories of BPSD symptoms most responsive to CIs (anxiety, hallucinations), memantine (agitation) and other drugs.…”
Section: Symptomatic Clinical Trials Using Cholinesterase Inhibitorsmentioning
confidence: 99%
“…Intervention protocols varied depending on the residents' needs, but could include various activities, such as walking the dog, playing with the dog, petting the dog, feeding it, talking to it, brushing it, reminiscing about pets, and talking to the dog handler. The researchers used the Cohen-Mansfield Agitation Inventory (CMAI) [32] to measure several behaviors, including physically aggressive behaviors. Nurses completed the CMAI at baseline, post-intervention, a 3-month followup, and a 6-month follow-up.…”
Section: Introducing Novel Stimuli Into the Environmentmentioning
confidence: 99%